2021
DOI: 10.3389/fcimb.2021.590874
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2-Indigenous Microbiota Nexus: Does Gut Microbiota Contribute to Inflammation and Disease Severity in COVID-19?

Abstract: Gut microbiome alterations may play a paramount role in determining the clinical outcome of clinical COVID-19 with underlying comorbid conditions like T2D, cardiovascular disorders, obesity, etc. Research is warranted to manipulate the profile of gut microbiota in COVID-19 by employing combinatorial approaches such as the use of prebiotics, probiotics and symbiotics. Prediction of gut microbiome alterations in SARS-CoV-2 infection may likely permit the development of effective therapeutic strategies. Novel and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 68 publications
3
48
0
Order By: Relevance
“…8 SARS-CoV-2 has been shown to use the receptors of angiotensin-converting enzyme-2 (ACE-2) as the cellular receptor system in the upper respiratory tract, and although the expression of ACE-2 in the gastrointestinal system is quite high, 9,10 the presence of GIS at varying rates and its effects on disease prognosis are still not fully explained. 11 In our study, it was observed that 71.4% of patients without GIS showed at least one of the symptoms after hospitalization and the frequency of development of intestinal disorders such as diarrhea-constipation increased as the disease severity increased. These findings suggest that the presence of GIS, which has a variable effect on the prognosis of the disease, may develop due to various factors (hospital infection, intensive antibiotic use, common proton pump inhibitor use, and specific treatments) rather than primary gastrointestinal system involvement of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…8 SARS-CoV-2 has been shown to use the receptors of angiotensin-converting enzyme-2 (ACE-2) as the cellular receptor system in the upper respiratory tract, and although the expression of ACE-2 in the gastrointestinal system is quite high, 9,10 the presence of GIS at varying rates and its effects on disease prognosis are still not fully explained. 11 In our study, it was observed that 71.4% of patients without GIS showed at least one of the symptoms after hospitalization and the frequency of development of intestinal disorders such as diarrhea-constipation increased as the disease severity increased. These findings suggest that the presence of GIS, which has a variable effect on the prognosis of the disease, may develop due to various factors (hospital infection, intensive antibiotic use, common proton pump inhibitor use, and specific treatments) rather than primary gastrointestinal system involvement of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 56%
“…Although SARS-CoV-2 often manifests itself only with upper respiratory tract symptoms and signs of lung damage, the presence of gastrointestinal symptoms (GIS) which might be associated with intestinal dysbiosis affects mortality and morbidity. [1][2][3] The finding of whole genome sequencing in the stools gives an insight that damages in the gut is a possibility. 4 Gastrointestinal symptoms mostly manifest themselves as nausea, vomiting, abdominal pain, and rarely diarrhea.…”
Section: Introductionmentioning
confidence: 99%
“…In this state, patients with severe COVID-19 may need to be admitted to the ICU for endotracheal intubation and mechanical ventilation. The evolution to COVID-19-ARDS is characterized by pulmonary edema, hypoxemia and inflammation, which are associated with changes in the lung microbiome (12). The microbiota is defined as the overall community of microbes included in a population (13), and the genetic content of the microbiota is known as the microbiome.…”
Section: Direct Lung Damage In Covid-19mentioning
confidence: 99%
“…Although much attention has been given to ACE2 expression in the respiratory tract, it is expressed at log-order higher levels in the intestinal system and gallbladder [ 45 ]. It has been demonstrated that, at least in mice, a deficiency of ACE2 causes inflammation, resulting in harmful alterations in the gut microbiome [ 46 ], which may be why gastrointestinal symptoms often accompany even mild cases of COVID-19.…”
Section: Connections Between the Lung And The Heartmentioning
confidence: 99%
“…Early observations from China have suggested that some COVID-19 patients suffered from dysbiosis with fewer Lactococcus and Bifidobacterium species in their gut. Infection with SARS-CoV-2 not only downregulates ACE2 expression in the lungs but also in the gut [ 45 ], and since ACE2 tightly controls the local production of antimicrobial peptides in the gut, this may have direct effects on the microbiome. Another explanation that has been put forward for gut dysbiosis is virus replication in the gut epithelial tissue.…”
Section: Probiotics and Covid-19mentioning
confidence: 99%